Remote Optical Diagnostics of Nonstationary Aerosol Media in a Wide Range of Particle Sizes - Kudryashova, Olga; Pavlenko, Anatoly; Vorozhtsov, Boris; Titov, Sergey; Arkhipov, Vladimir; Bondarchuk, Sergey; Maksimenko, Eugeny; Akhmadeev, Igor; Muravlev, Eugeny (IntechOpen, 2012)
None